Impact of Storage Temperature on Pollen Viability and Germinability of Four Serbian Autochthon Apple Cultivars - Ćalić, Dušica; Milojević, Jelena; Belić, Maja; Miletić, Rade; Zdravković-Korać, Snežana (Frontiers in Plant Science, 2021)
Globalization has drastically reduced the number of autochthon apple cultivars in the Serbian market and most of them have nearly disappeared. However, some of these cultivars, such as Petrovača, Budimka, Kolačara Pozna and Kožara, have extraordinary quality, good pomological characteristics and pest, and disease resistance. The present study was conducted to develop a protocol for the storage of pollen for further use in the conservation and breeding of these cultivars. Viability and germination of the mature pollen were tested in vitro, at four storage temperatures (20°C, 4°C, −20°C, −80°C), right after harvest or 1, 2, 3, 4, 5, and 6 months after storage. Differences in fresh pollen viability and germination between cultivars were statistically significant and ranged from 60% to 88% and 59% to 98%, respectively. Fresh pollen of cv. Budimka showed the highest viability and germination in comparison with other cultivars, especially cv. Kožara. Pollen viability and germination decreased over storage period and it was the lowest after 6 months of storage at room temperature in all tested cultivars. Storage at 4°C prolonged the pollen viability and germinability 1-5 fold, depending on the cultivar and treatment duration. However, pollen longevity of all cultivars was significantly extended when stored at −20°C or −80°C. After 6 months, pollen of cv. Budimka stored at −20°C and −80°C showed 14-15 fold higher germination rates in relation to pollen storage at room temperature for the same period of time. The results of the present study suggest that the pollen of these apple cultivars could be efficiently maintained at −20°C and further used for breeding purposes e.g. for crossings between cultivars that flower at different times of the year.